Establishment of in vitro regeneration and transformation protocol to develop salinity stress tolerant tomato (Lycopersicon esculentum Miller) - Ferdous, Manzur -E- Mohsina (BRAC Univeristy, 2018)
This thesis report is submitted in partial fulfilment of the requirement for the degree of M.Sc in Biotechnology, 2012.